CISSP - Greene, Sari Stern, 1957- (LiveLessons (Indianapolis, Ind.), 2016)
CISSP Complete Video Course contains 24 hours of training with content divided into 9 lessons with 94 video sub-lessons. The videos consist of live trainer discussions, screencasts, animations, and live demos. The video lessons in this course review each exam objective so you can use this course as a complete study tool for taking the CISSP exam. Instruction throughout offers detailed explanations, demos, tips, and more. CISSP Exam Prep LiveLessons provides 7 hours of deep-dive training on common CISSP exam traps, pitfalls, and difficulties. The goal of theCISSP Exam Prep LiveLessonsis to give you the edge you need to pass the rigorous CISSP exam and successfully gain certification. This course is designed to familiarize you with test-taking strategies, review “must know” and “challenging” concepts, practice answering exam questions, and most importantly, give you the confidence to pass your exam with flying colors. This course is NOT designed to be a comprehensive study guide. Instead we will be focusing on components of the ISC2 CBK (common body of knowledge) that fall into one of four categories. Sari Greene, best-selling author of theCISSP Complete Video Course, will also walk you through practice questions throughout, highlighting how to answer difficult questions and reduce errors. She will end with a discussion on winning exam day strategies, so you can make the most of your time as you prepare. This is targeted exam prep training, so you can make the most of your knowledge when taking the test.